Strong Was Her Faith Women of the New Testament. - Kalas, J. Ellsworth (: Abingdon Press, 2012)
Stories of Women Whose Faith in God Made a Difference.
Cover; Book Information; Copyright; Dedication; Contents; Foreword; 1. Elizabeth: A Friend in Need; 2. Anna: She Knew How to Wait; 3. Martha, the Disciplined; 4. Mary, the Extravagant; 5. The Mighty Widow; 6. The Anonymous Evangelist; 7. Mary Magdalene: When Love Is Greater Than Faith; 8. Mary, the Mother of Mark; 9. Dorcas: Worth a Miracle; 10. Lydia, the Businesswoman; 11. Mary in Life and Legend; 12. Why Mary?; Study Guide; Notes; Back Cover
Description based upon print version of record.
Master record variable field(s) change: 082
Keywords: Women in the Bible; RELIGION / Biblical Studies / New Testament; Women in the Bible; Electronic books; Electronic books